Роль інформаційно-комунікаційних технологій в забезпеченні захисту інформації на рівні територіальних громад - Горбаченко, Станіслав Анатолійович; Horbachenko, Stanislav A.; Соколов, Артем Вікторович; Sokolov, Artem V.; Клєвцєвич, Наталія Анатоліївна; Klievtsievych, Nataliia A. (My University, 2025)
Метою даної роботи є обґрунтування теоретичних та практичних основ впровадження інструментів захисту інформації на рівні територіальної громади. У статті доведено, що ІКТ відіграють важливу роль у безпечному обміні інформацією на рівні територіальних громад. Визначені ІКТ що використовуються у розвитку ТГ. Систематизовано напрямки обміну інформацією на рівні ТГ. Зазначено, що використання розглянутих ІКТ при обміні інформацією на рівні ТГ відбувається за кількома напрямками. Обґрунтовано, важливість та необхідність захисту інформації на рівні ТГ. Розглянуті практичні застосування ІКТ у розвитку ТГ. Проведено групування засобів захисту інформації на рівні ТГ, зокрема виділено 5 таких груп (фізичні, комп’ютерні, організаційні, технологічні, соціально-психологічні). Зроблено висновок, що захист інформації на рівні територіальної громади є критично важливим як з погляду приватності та безпеки громадян, так і для забезпечення нормальної роботи адміністративних та соціальних служб, а також для запобігання потенційним кіберзагрозам та злочинам. Криптографічні засоби є одним з найважливіших інструментів, які використовуються для забезпечення захисту інформації, зокрема, у інформаційно-телекомунікаційних системах ТГ. The theoretical basis of this scientific work consists of the best practices of safe exchange of information in territorial communities and protection of confidential data of citizens and municipal services from potential threats given in recent papers of a theoretical and practical nature. To carry out this scientific work and achieve the goal, the article uses methods of graphic interpretation of the results of analysis and generalization, methods of monographic analysis, and synthesis. It has been proven that ICT plays an important role in the secure exchange of information. The ICT used in the development of TС have been identified. Areas of information exchange at the TС level have been systematized. It is noted that the use of the considered ICT in the exchange of information at the TС level takes place in several directions: in the management of the TС directly; when interacting with other TС; when interacting with central authorities. It was noted that the use of digital technological solutions in the management of the TС is envisaged at several levels: at the level of the residents of the TС; at the level of the business environment; at the level of local authorities; at the level of TС as a whole. The importance and necessity of protecting information at the TС level is justified. Practical applications of ICT in the development of TС are considered. Grouping of methods of information protection at the TС level was carried out, in particular, 5 such groups were selected (physical, computer, organizational, technological, socio-psychological). It was concluded that the protection of information at the level of the territorial community is critically important both from the point of view of privacy and security of citizens, and for ensuring the normal operation of administrative and social services, as well as for preventing potential cyber threats and crimes. Cryptographic means are one of the most important tools used to ensure information protection, in particular, in information and telecommunication systems of the TG.
Горбаченко С. А. Роль інформаційно-комунікаційних технологій в забезпеченні захисту інформації на рівні територіальних громад / С. А. Горбаченко, А. В. Соколов, Н. А. Клєвцєвич // Економічний вісник НТУУ "Київський політехнічний інститут". - 2024. - No 29. - С. 169-176. - Режим доступу: https://doi.org/10.20535/2307-5651.29.2024.308831 ; https://hdl.handle.net/11300/29698
Keywords: інформаційно-комунікативні технології; ІКТ; цифрові технології; цифрові рішення; територіальні громади; захист інформації; обмін інформацією; information and communication technologies; ICT; digital technologies; digital solutions; territorial communities; information protection; information exchange